(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2010)
Phenomenology is a relatively new philosophy with some distinguishable features and when social scientists base their research methods on that perspective sometimes variations in methods take place that are attributed to phenomenology but the variations are not necessarily consistent with the phenomenological perspective nor with good scientific practices. When the modifications are not consistent it is usually because the claim is based on the failure to distinguish between phenomenology as a philosophy and phenomenology as a theory of science. Such ambiguities can arise because there is not as yet a fully developed phenomenological theory of science even though its articulation is sorely needed. In this article, some examples of the types of methodical errors practiced by promoters of the phenomenological approach that exist in the literature are examined. The conclusion reached is that the methodical errors are due to violations of principles of good science and the modifications are not consistent with the phenomenological perspective.